Protein Engineering Techniques Gateways to Synthetic Protein Universe - Poluri, Krishna Mohan; Gulati, Khushboo; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This brief provides a broad overview of protein-engineering research, offering a glimpse of the most common experimental methods. It also presents various computational programs with applications that are widely used in directed evolution, computational and de novo protein design. Further, it sheds light on the advantages and pitfalls of existing methodologies and future perspectives of protein engineering techniques.
World of Proteins: Structure-Function relationships and Engineering techniques -- Expanding the Synthetic Protein universe by guided Evolutionary Concepts -- Rationale Designing of Novel Proteins through Computational Approaches -- Generating the Fancy Protein Basket with De novo Approach -- Biotechnological Applications of Protein Engineering Methods.
Keywords: Computational intelligence; Biotechnology; Pharmaceutical chemistry; Bioinformatics; Biomedical engineering; Computational Intelligence; Biotechnology; Pharmaceutics; Computational and Systems Biology; Biomedical Engineering and Bioengineering